2020
DOI: 10.5606/tgkdc.dergisi.2020.18508
|View full text |Cite
|
Sign up to set email alerts
|

The role of endobronchial ultrasonography elastography for predicting malignancy

Abstract: Bu çalışmada endobronşiyal ultrasonografi elastografinin maligniteyi öngörmedeki rolü araştırıldı. Ça lış ma pla nı: Ocak 2016 -Aralık 2016 tarihleri arasında, endobronşiyal ultrasonografi eşliğinde transbronşiyal iğne aspirasyon biyopsisi ile 119 ardışık hastadan (69 erkek, 50 kadın; ort. yaş 63.2±12.4 yıl; dağılım 16-86 yıl) toplam 221 lenf nodu çalışmaya alındı. Lenf nodları işlem öncesinde elastografi ile renklerine göre dört kategoride skorlandı. Gerginlik oranı, üç ölçüm sonrasında ilgili bölgeye göre he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…Controversially, other studies showed sensitivity or speci city of EBUS-elastography in the diagnosis of malignant lymph node were around 75% -87% or 65%-68% (Caglayan et al 2020;Fournier et al 2019). The discrepancy could be partly due to the different way to interpret the image results in EBUSelastography.…”
Section: Discussionmentioning
confidence: 97%
“…Controversially, other studies showed sensitivity or speci city of EBUS-elastography in the diagnosis of malignant lymph node were around 75% -87% or 65%-68% (Caglayan et al 2020;Fournier et al 2019). The discrepancy could be partly due to the different way to interpret the image results in EBUSelastography.…”
Section: Discussionmentioning
confidence: 97%
“…A NPV of 100% demonstrated that EBUS elastography could decrease the number of unnecessary aspirations and the total examination time. Controversially, other studies have indicated approximately 75% to 87% sensitivity and 65% to 68% specificity of EBUS elastography in diagnosing malignant lymph nodes [ 30 , 31 ]. This discrepancy could be partly explained by different interpretations of the EBUS elastography images.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 1 shows the flow chart of the study selection. Finally, 17 publications were included in this meta-analysis [14][15][16][23][24][25][26][27][28][29][30][31][32][33][34][35][36].…”
Section: Study Selectionmentioning
confidence: 99%
“…The 17 enrolled studies were published between 2014-2020 and written in English [14][15][16][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. A total of 1360 patients with 2307 hilar and mediastinal LNs were included in these studies.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation